Η μετανάστευση των νέων επιστημόνων και εργαζομένων στα χρόνια της οικονομικής κρίσης - Βήτου, Μαριάνα (Εθνικό Μετσόβιο Πολυτεχνείο. Σχολή Εφαρμοσμένων Μαθηματικών και Φυσικών Επιστημών, 2018)
This post-graduate thesis aims to find solutions / proposals that will potentially hinder or even reverse the flight of human capital that has been observed following the onset of the financial and economic crisis that has hit our country since 2010, the current reality of the migration of young workers and scientists is analyzed by using data gathered through hundreds of responses to a questionnaire created and distributed online for this purpose. Reference is made to past migratory flows, to the causes and effects of the migratory wave we are experiencing today, as well as to the efforts of the state to combat unemployment and, consequently, the immigration of Greeks abroad. Their potential effectiveness is discussed in this text, as are the efforts of citizens through their participation in collective-cooperative economies. All the above, after being analyzed with a critical eye, gave the opportunity to formulate appropriate proposals-solutions. The solutions proposed are based on the implementation of the "Worth-living Integrated Development" (Rokos, 2003), aiming to create a country worth living, where everyone will feel security, freedom, harmony and respect. Only so will the Greeks remain in their homeland.